A Pragmatic Analysis of Deixis and Reference on Billie Eilish Song: Bad Guy & When the Party's Over - Kakiay, Theresa Welma; Maitimu, Laura Sansa (Huele: Journal of Applied Linguistics, Literature and Culture, 2021)
The aim of this Pragmatic study is to examine the different types of deixis from Cruse theory and references using pragmatic analysis in When The Party's over and Bad Guy songs under descriptive qualitative. The result found from the analysis that both songs use all five types of deixis. The personal deictic words occur first person that mostly refer to the singer or the songwriter, then second person is referring to the addressee that remarked by you and your and the last is third person It or she is referring to something or someone that become the main thing or character in songs. Furthermore, the use of spatial deixis is less for both of songs. only one projected term that included in both songs. Next, temporal deixis that appeared in both songs is different. Temporal deixis has two types of deixis but in Bad Guy only occur one type of temporal deixis which is verb tense while in When the party's over the pure deictic and verb tense occurred. The last, the social and discourse deixis with different deictic words occurred also in both songs. The result hopefully could be the reference for students in Linguistic Field in analyzing the written discourse with Pragmatic Approach. Keyword: deixis, pragmatic, reference, song